A extrafiscalidade no ICMS - Bolognese, Marcelo (2023)
This work aims to analyze extra-taxation in the Brazilian Tax System, its origin, constitutional principles with points of contact with the theme, as well as its forms and techniques of applicability, such as the establishment of calculation basis, use of differentiated rate, immunity, exemption, deferral, suspension, presumed and granted credit, and special taxation regime. The concept of tax, of tax, with a greater focus on ICMS, which was chosen to be the protagonist of this research, was briefly addressed. In the next moment, but which still consists of the purpose of this thesis, we identified the hypotheses of the extra-taxation of ICMS, based on the text of the Federal Constitution, passing through the Complementary Laws, continuing the analysis in the ordinary law of São Paulo, reaching the exemptions contained in the ICMS/SP Regulation. After each of the hypotheses was pointed out, our study proposed to assign a classification of the nature of this extra-taxation, and at the end, present the classification based on the objectives of the State, duly contained in the Greater Charter, in articles 3 and 6, when dealing with social rights in general; in Article 23, when dealing with the ordinary competence of taxing entities; going through Article 170, which deals with the economic and financial order; as well as in article 218 that establishes the mandatory command of the State to promote and encourage scientific and technological research and development; and, finally, in Article 219, which elevates the internal market (and its protection) at the level of national heritage